SSL-TLS security flaw : a study of the RSA "freak" attack - Low, John Kah Yong (Nanyang Technological University, 2020)
RSA, a cryptography algorithm that was developed in 1977, still remains as one of the world’s most powerful cryptography algorithm till date. Applications such as e-commerce platform, government websites, and bank websites use RSA cryptography algorithm to secure sensitive data over the Internet via the SSL/TLS protocol. With a heavy increase in network traffic over the years, this cryptographic protocol became even more important as it helps to provide a safe and secure environment for network communications.